Leaching characteristics, toxicity and adsorption capacities of micro-plastic beads - Yong, Rachel Jie Ying (2018)
Plastic pollution is a ubiquitous and growing global problem. Past studies have shown that not only are plastics a source of chemical contaminants to environment, but also a sink of organic pollutions in the environment. Typically, polymers and plasticizers can be released from plastics into the aquatic environment, which might then be directly ingested by humans via usage of plastic products. Moreover, harmful organic contaminants present in the environment can be adsorbed onto plastics or polymers, which then get transported along with the plastics ingested by aquatic organisms, and eventually affecting humans as well. These phenomena are undesirable and hence this project aimed to investigate both the leaching characteristics and adsorption capacities of plastics. In this work, six common plastics (PS, PE, PP, PC, PET and PVC) were chosen. After an 28-hour exposure to deionised water, leachates were analysed for their size, morphology and elemental components. In the analysis of molecular weights, two peaks were found, which suggest leachates are mainly 20K or very small (MW<1000). Elements detected through EDX analysis suggest the presence of common additives CaCO3, SiO2, CaSiO3 and NaCl in the plastics. Hence, GC-MS and LC-QTOF were employed to identify the small (MW<1000) but complex mixture of leachate compounds released in plastic leachates. All plastics leachates were found to contain DEHP, BPA and DIBP, while DIBP was only identified in PET leachate. Besides, compared with leaching in synthetic seawater, less quantities of plasticizers were yielded in deionised water. From the cytotoxicity test, PP was found to be the most toxic to MCF-7 cells at all test concentrations. PAHs were chosen to quantify relationships between different types of plastic and organic contaminants in this project. Our data suggest that the molecular weight and Log KOW of PAHs affect their adsorption by plastics. A lighter compound has a lower Log KOW value and would reach saturation faster. For future study, the role of various environmental conditions on leaching and adsorption could be explored. The effect of plastics on cell metabolism could also be investigated.